The FDA's Solution to Adaptive AI: Understanding the Predetermined Change Control Plan (PCCP) - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The rapid integration of Artificial Intelligence and Machine Learning AI/ML into Software as a Medical Device SaMD has presented a profound challenge to trad...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care